The leader's brain : enhance your leadership, build stronger teams, make better decisions, and inspire greater innovation with neuroscience - Platt, Michael L. (Ascent Audio, 2022)
Leadership is a set of abilities with which a lucky few are born. They're the natural relationship builders, master negotiators and persuaders, and agile and strategic thinkers. The good news for the rest of us is that those abilities can be developed. In The Leader's Brain: Enhance Your Leadership, Build Stronger Teams, Make Better Decisions, and Inspire Greater Innovation with Neuroscience, Wharton Neuroscience Initiative director Michael Platt explains how. Over two decades as a professor and practitioner in neuroscience, psychology, and marketing, Platt's pioneering research has deepened our understanding of how key areas of the brain work-and how that understanding can be applied in business settings. In The Leader's Brain, Platt explains: why two managers, when presented with the same set of information, make very different decisions; why some companies (Apple) build strong social and emotional connections with their customers and others do not (Samsung); how some of the most significant events in sports history, like the "Miracle on Ice," contain insights for how to build a team; and why even some of the most visionary business leaders can make disastrous decisions, and how to fix that. The Leader's Brain relates findings like these, and many more, to help enhance leadership in an ever-shifting world entering a "new normal.".